Identification of Circulating Tumor DNA for the Early Detection of Small-cell Lung Cancer - Fernandez-Cuesta, Lynnette; Perdomo, Sandra; Avogbe, Patrice H; Leblay, Noemie; Delhomme, Tiffany M; Gaborieau, Valerie; Abedi-Ardekani, Behnoush; Chanudet, Estelle; Olivier, Magali; Zaridze, David; Mukeria, Anush; Vilensky, Marta; et al. (EBioMedicine, 2016)
Circulating tumor DNA (ctDNA) is emerging as a key potential biomarker for post-diagnosis surveillance but it may also play a crucial role in the detection of pre-clinical cancer. Small-cell lung cancer (SCLC) is an excellent candidate for early detection given there are no successful therapeutic options for late-stage disease, and it displays almost universal inactivation of TP53. We assessed the presence of TP53 mutations in the cell-free DNA (cfDNA) extracted from the plasma of 51 SCLC cases and 123 non-cancer controls. We identified mutations using a pipeline specifically designed to accurately detect variants at very low fractions. We detected TP53 mutations in the cfDNA of 49% SCLC patients and 11.4% of non-cancer controls. When stratifying the 51 initial SCLC cases by stage, TP53 mutations were detected in the cfDNA of 35.7% early-stage and 54.1% late-stage SCLC patients. The results in the controls were further replicated in 10.8% of an independent series of 102 non-cancer controls. The detection of TP53 mutations in 11% of the 225 non-cancer controls suggests that somatic mutations in cfDNA among individuals without any cancer diagnosis is a common occurrence, and poses serious challenges for the development of ctDNA screening tests.
Keywords: nádorový supresorový protein p53; DNA, Neoplasm; Early Detection of Cancer; Leukocytes; Male; Small-cell lung cancer; mužské pohlaví; nádory plic; studie případů a kontrol; mutace; TP53 mutations; Tumor Suppressor Protein p53; malobuněčný karcinom plic; ctDNA; časná detekce nádoru; cfDNA; Biomarkers, Tumor; Neoplasm Staging; ženské pohlaví; nádorové biomarkery; Mutation; Humans; Early detection; Screening; DNA nádorová; staging nádorů; Small Cell Lung Carcinoma; Female; leukocyty; Lung Neoplasms; lidé; Case-Control Studies